2011
DOI: 10.1007/s00586-011-2097-7
|View full text |Cite
|
Sign up to set email alerts
|

Physical fitness, rather than self-reported physical activities, is more strongly associated with low back pain: evidence from a working population

Abstract: Introduction Physical activity is suggested to be important for low back pain (LBP) but a major problem is the limited validity of the measurement of physical activities, which is usually based on questionnaires. Physical fitness can be viewed as a more objective measurement and our question was how physical activity based on self-reports and objective measured levels of physical fitness were associated with LBP. Materials and methods We analyzed cross-sectional data of 1,723 police employees. Physical activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 40 publications
1
57
1
2
Order By: Relevance
“…In addition, the total volume of LTPA did not predict hospitalization due to back disorders in the current study cohort [6]. A recent cross-sectional study among police employees [9] found differences between the associations of the volume and intensity of physical activity with LBP. Persons with high metabolic equivalent hours of high intensity physical activity had a lower risk (albeit statistically non-significantly) for functionally limiting LBP compared to those with some metabolic equivalent hours, although the overall volume of activity increased the risk.…”
Section: Discussioncontrasting
confidence: 63%
“…In addition, the total volume of LTPA did not predict hospitalization due to back disorders in the current study cohort [6]. A recent cross-sectional study among police employees [9] found differences between the associations of the volume and intensity of physical activity with LBP. Persons with high metabolic equivalent hours of high intensity physical activity had a lower risk (albeit statistically non-significantly) for functionally limiting LBP compared to those with some metabolic equivalent hours, although the overall volume of activity increased the risk.…”
Section: Discussioncontrasting
confidence: 63%
“…Physical activity has also been recommended as a form of rehabilitation for and in the prevention of low back pain [9]. Other studies determined that a high level of physical fitness is related to a decreased incidence of spine-related pain [10].…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to the fact that different individual spine curves require different individual stabilizing musculature [49][50][51][52][53][54].…”
Section: Compensationmentioning
confidence: 95%